2012
DOI: 10.21273/hortsci.47.9.1320
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Socioeconomic Challenges to Setting and Implementing Priorities in North American Rosaceous Fruit Breeding Programs

Abstract: Rosaceous crops (e.g., almond, apple, apricot, caneberry, cherry, pear, peach, plum, rose, and strawberry) contribute to human health and well-being and collectively constitute the economic backbone of numerous North American rural communities. We conducted a survey of U.S. and Canadian rosaceous fruit crop breeders to assess priority setting in their programs, sources of information for setting priorities, and challenges in making technical and management decisions. Input from producers and consumers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 3 publications
2
18
0
Order By: Relevance
“…Overall, we found that turfgrass seed breeders rated the producers/growers and consumers as more important parties compared with other interested parties. This finding, similar to the results of a previous study of rosaceous fruit breeding programs (Yue et al, 2012), suggests that breeders are aware that the turfgrass industry is a market-driven industry and that they recognize consumers' needs and acceptance as the most important indicators for market success. Furthermore, breeders care about the benefits of the producers/growers; therefore, their breeding efforts should aim to provide producers/ growers with more profits.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Overall, we found that turfgrass seed breeders rated the producers/growers and consumers as more important parties compared with other interested parties. This finding, similar to the results of a previous study of rosaceous fruit breeding programs (Yue et al, 2012), suggests that breeders are aware that the turfgrass industry is a market-driven industry and that they recognize consumers' needs and acceptance as the most important indicators for market success. Furthermore, breeders care about the benefits of the producers/growers; therefore, their breeding efforts should aim to provide producers/ growers with more profits.…”
Section: Discussionsupporting
confidence: 86%
“…In general, resource availabilities were rated as the most challenging when determining the program priorities; costs, followed by resource allocation and resource availability, were rated as the most challenging factors when breeders were implementing priorities. Although turfgrass breeders encounter a variety of challenges different from those of breeding programs for rosaceous crops (Yue et al, 2012), resource-related challenges were still among the most influential factors when making decisions about selecting traits. Breeding programs with larger sizes were less concerned with the technical challenges (such as identifying new sources of genes, documentation of existing germplasms, and evaluating new sources of germplasms) and societal challenges (for example, finding niche market potential); however, resourcerelated challenges were considered more important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DA scores are often correlated with compositional, analytical or instrumental determinations to provide insight into the aroma/flavor compounds or textural measurements which account for the perceived sensory attributes. Ultimately this information must be combined with consumer acceptability in order to identify and breed for traits that are most important to consumers . While product developers can manipulate food formulations to achieve the ‘ideal’ characteristics, the fruit breeder must rely on breeding and selection of fruit with the most appropriate set of characteristics available from genetic segregation …”
Section: Introductionmentioning
confidence: 99%
“…Ultimately this information must be combined with consumer acceptability in order to identify and breed for traits that are most important to consumers. 4,5 While product developers can manipulate food formulations to achieve the 'ideal' characteristics, the fruit breeder must rely on breeding and selection of fruit with the most appropriate set of characteristics available from genetic segregation. 6 Since fruit is only available in limited quantities in the early stages of apple selection, it is necessary to estimate consumer acceptance using a small in-house panel.…”
Section: Introductionmentioning
confidence: 99%